2022
DOI: 10.1186/s12905-021-01588-8
|View full text |Cite
|
Sign up to set email alerts
|

The best postoperative adjuvant therapy for patients with early stage cervical adenosquamous carcinoma

Abstract: Background Cervical adenosquamous carcinoma (ASC) was previously thought to be a subtype of cervical adenocarcinoma, but recent studies have found that the clinical features of the two diseases are different. Moreover, the pathological characteristics, survival, prognosis, and optimal ASC therapy remain unknown. This study aims to retrospectively analyze the postoperative survival of patients with early-stage ASC and to evaluate their condition after treatment with postoperative concurrent chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It might owe to the early diagnosis and comprehensive adjuvant treatment of married patients [30,31]. For adjuvant treatment, some studies showed that chemotherapy was beneficial to prognosis [32], while others reported that postoperative radiotherapy could improve the survival rate of patients with early cervical cancer [33]. Our study found that patients receiving postoperative radiotherapy have better CSS, which needs more confirmation studies.…”
Section: Discussionmentioning
confidence: 49%
“…It might owe to the early diagnosis and comprehensive adjuvant treatment of married patients [30,31]. For adjuvant treatment, some studies showed that chemotherapy was beneficial to prognosis [32], while others reported that postoperative radiotherapy could improve the survival rate of patients with early cervical cancer [33]. Our study found that patients receiving postoperative radiotherapy have better CSS, which needs more confirmation studies.…”
Section: Discussionmentioning
confidence: 49%
“…A significant number of studies examining the role of adjuvant therapy in early stage cervical cancer were conducted according to the FIGO 2009 staging criteria and included lymph node positive patients. [14][15][16] The patients in our study were staged according to the current FIGO staging system, which was revised in 2018 and included pelvic/paraaortic lymph node involvement in the staging. Therefore, it does not include lymph node positive patients.…”
Section: Discussionmentioning
confidence: 99%